فعالية برنامج إرشادي قائم على السيكودراما للتخفيف من حدة بعض المشكلات السلوكية عند طلاب المرحلة الإعدادية - عزات جمعة, أمجد (جامعة الوادي University of Eloued, 2016)
هدفت الدراسة إلى التعرف على فعالية برنامج إرشادي قائم على السيكودراما في التخفيف من حدة بعض المشكلات السلوكية عند طلاب المرحلة الإعدادية. تكونت عينة الدراسة من24 طالباً تم تقسيمهم إلى مجموعتين؛ الأولى تجريبية وقوامها 12 طالباً، والثانية ضابطة، وقوامها 12 طالباً، حيث تم اختيارهم من بين 160 طالب من مدرسة ذكور رفح الإعدادية (ج) التابعة لوكالة الغوث بغزة، ممن حصلوا على أعلى الدرجات على مقياس المشكلات السلوكية. واستخدم الباحث في دراسته الحالية عدة أدوات للتحقق من صحة فروض الدراسة منها: (استمارة مسح المشكلات السلوكية ومقياس المشكلات السلوكية (من إعداد الباحث) والبرنامج الإرشادي القائم على السيكودراما (إعداد الباحث). بعد استخدام الباحث لأدوات الدراسة وإجراء المعالجة الإحصائية للبيانات تم التوصل إلى وجود فروق ذات دلالة إحصائية بين أفراد المجموعتين التجريبية والضابطة في حدة المشكلات السلوكية بعد تطبيق البرنامج السيكودرامي لصالح أفراد المجموعة التجريبية، ووجود فروق ذات دلالة إحصائية بين أفراد المجموعة التجريبية في حدة المشكلات السلوكية بين التطبيق القبلي والبعدي لمقياس المشكلات السلوكية، وعدم وجود فروق ذات دلالة إحصائية بين أفراد المجموعة التجريبية في حدة المشكلات السلوكية بين التطبيق البعدي والتتبعي بعد شهرين لمقياس المشكلات السلوكية. The Purpose of the Study was to know the effectiveness and efficacy of psychodrama to reduce some behavioral problems for the preparatory students. The sample of this study consisted of (24) students that have behavioral problems. This sample was divided into 12 students as an experimental group, and 12 students as a control group. The researcher used some tools of this study; such as, behavioral problems survey form, the scale of behavioral problems and the program of psychodrama which was all prepared by the researcher. The statistical method used in the study was Mann-Whitney-U Test, Wilcoxon Signed-Rank Test, Pearson's Correlation Coefficient, R.The results of the study revealed: There were significant differences between the members of both experimental and control group in the severity of the behavioral problems after the applying of psychodramitc program on favor of the experimental group members. There were significant differences among experimental group members in the severity of behavioral problems between the first and second application of the behavioral problems scale.. There were no significant differences for experimental group members in the severity of behavioral problems between the second application of the behavioral problems scale and the serial study among two months.
مقال
Keywords: لسيكودراما – المشكلات السلوكية – المرحلة الإعدادية; Psychodrama – Behavioral Problems – preparatory Students